2020
DOI: 10.1111/1440-1681.13309
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Diosmetin exerts cardioprotective effect on myocardial ischaemia injury in neonatal rats by decreasing oxidative stress and myocardial apoptosis

Abstract: Myocardial injury caused by the myocardial ischaemia (MI) is still a troublesome condition in the clinic, including apoptosis, oxidative stress and inflammation. Diosmetin inhibits the cellular apoptosis and inflammatory response and enhances antioxidant activity. So, this study was designed to investigate the cardioprotective effects of diosmetin on MI model neonatal rats. Forty Sprague Dawley (SD) rats 7 days old were randomly divided into five groups. Four groups of rats received diosmetin (50, 100, and 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…A large number of pharmacological investigations have shown that diosmetin has anti-tumor, anti-acute kidney injury and anti-acute lung injury activities (Chen et al, 2019;Liu, Ci, Wen & Peng, 2018;Yang, Li, Yu, Yi & Huang, 2017). The previous studies also indicated that diosmetin can attenuate oxidative stress and decrease level of proinflammatory cytokine (Mo, He, Zhang, Lei & Luo, 2020;Zaragozá, Villaescusa, Monserrat, Zaragozá & Álvarez-Mon, 2020). In our experiment, we studied and reported the effects and potential molecular mechanisms of diosmetin treating IBD.…”
Section: Introductionmentioning
confidence: 79%
“…A large number of pharmacological investigations have shown that diosmetin has anti-tumor, anti-acute kidney injury and anti-acute lung injury activities (Chen et al, 2019;Liu, Ci, Wen & Peng, 2018;Yang, Li, Yu, Yi & Huang, 2017). The previous studies also indicated that diosmetin can attenuate oxidative stress and decrease level of proinflammatory cytokine (Mo, He, Zhang, Lei & Luo, 2020;Zaragozá, Villaescusa, Monserrat, Zaragozá & Álvarez-Mon, 2020). In our experiment, we studied and reported the effects and potential molecular mechanisms of diosmetin treating IBD.…”
Section: Introductionmentioning
confidence: 79%
“…This has not always been the case, in sepsis-induced acute kidney injury (AKI), the expression of the Nrf2/HO-1 signal axis was enhanced after diosmetin treatment, which were reversed by siNrf2 [26]. In addition, diosmetin also showed cardioprotective effects in MI model neonatal rats, accompanied by a decrease in p-Nrf2/Nrf2 [27]. Diosmetin protects against LPS-induced acute lung injury (ALI) via increasing the expression of Nrf2 along with its target gene HO-1 and blocked the activation of NLRP3 inflammasome both in vivo and in vitro [28].…”
Section: Discussionmentioning
confidence: 99%
“…Reports suggest that a small dose of diosmetin protects against oxidative stress injury in myocardial ischaemia and inhibits cardiomyocyte apoptosis in rats. 29 Fifty rats were randomly allocated to five groups (10 rats/group):…”
Section: Dose Selection With Grouping and Treatmentmentioning
confidence: 99%